2008
DOI: 10.1007/s12046-008-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface deformation and the role of surface texture—A study with Cu pins and steel plates

Abstract: The extent of subsurface deformation below the worn surface influences friction and transfer layer formation during sliding. Thus, in this study, the extent of plastic deformation and strain localization events that occur at various depths beneath the worn surface in the subsurface zones of Cu pins slid against steel plate with various surface textures have been determined using simple metallographic techniques. Results showed that the magnitude of plastic strain gradient and the depth of highly deformed zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…We can only speculate why the grains in the subsurface area for A r = 0.4 are at a preferential angle towards to sliding surface. In the literature, a similar phenomenon was described for pin-on-disc experiments [18,19,21,42]. Even though these authors offer different reasons for a grain orienting and bending, the observation itself can easily be rationalized for such unidirectional sliding tests.…”
Section: Subsurface Microstructuresupporting
confidence: 62%
“…We can only speculate why the grains in the subsurface area for A r = 0.4 are at a preferential angle towards to sliding surface. In the literature, a similar phenomenon was described for pin-on-disc experiments [18,19,21,42]. Even though these authors offer different reasons for a grain orienting and bending, the observation itself can easily be rationalized for such unidirectional sliding tests.…”
Section: Subsurface Microstructuresupporting
confidence: 62%
“…In general, a wear surface can be divided into three different zones: the undisturbed base material, the deformed intermediate region of the base material, and the worn surface that usually contains counterface material [53,54]. These three zones are schematically shown in Fig.…”
Section: Wear and Friction Of Aluminum Alloys And Compositesmentioning
confidence: 99%
“…Other publications reported similar deformations caused by plastic flow in the surface of steels, such as the ball impact test on plastic steels [ 18 ], and steel cutting operations [ 19 , 20 , 21 ]. It was also found that the surface texture influences the plastic deformation in ductile materials after sliding [ 22 ]. M. Sedlacek et al [ 23 ] investigated the correlation between surface roughness parameters and friction and found that the surfaces with higher kurtosis and negative skewness values tend to reduce friction.…”
Section: Introductionmentioning
confidence: 99%